Letters of Obligation: Debt, Trust and Moral Economy in the Lekhapaddhati (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
This paper examines the letters of debt and obligation preserved in the Lekhapaddhati, a Sanskrit-Gujarati manual of letter writing from early medieval Western India, precisely in the Gujarat. The time and place of its origin are linked to the dynasties of the Cāulukyas and their successors, the Vāghelās, whose rulers are frequently mentioned in the Lekhapaddhati. These letters, written in ‘mixed language’, offer a rare window into how debt was negotiated, acknowledged, and emotionally experienced in everyday life. Rather than viewing them as administrative or legal correspondence, this study reads them as reflections of a moral economy, where the circulation of money was governed as much by trust, honour, and social reputation. By analyzing two contrasting mortgage correspondences from the Lekhapaddhati, Gṛihaḍḍāṇaka Patra Vidhi Yathā and Gṛihaḍūli Patra Yathā, this paper explores the structural composition of the letters, identities of creditors and debtors, the role of witnesses and intermediaries, and the diverse emotions through which obligation and trust were articulated. Through the comparative analysis of both correspondences, the paper seeks to reconstruct the everyday texture of credit relations and the ethical world within they were embedded.
Keywords: Lekhapaddhati; letter-writing; debt; moral economy; credit system